Drivers of AI Adoption: The Role of Innovation Attributes, Organizational Capability, and the External Environment - Hashmi, Maria; Tubastuvi, Naelati (Pattimura University, 2026)
Artificial Intelligence continues to reshape the ICT sector in Pakistan, yet organizations differ widely in how and why they adopt this technology. This study explores the key drivers of AI adoption by focusing on national ICT professionals who work directly with digital systems and emerging technologies. A total of 110 valid responses were collected through an organized online survey using purposive sampling. The investigation was guided by Technology Organization Environment framework combined with innovation characteristics from Diffusion of Innovation theory. The variables examined include the perceived suitability of AI to current systems, the benefits and complexity of adopting AI, organizational technical capability, and external environmental pressures. Data analysis involved Smart PLS-SEM, which facilitated reliability and validity assessment along with hypothesis evaluation. The outcomes highlight that seamless compatibility with existing infrastructure plays a key role in encouraging AI adoption, offers clear operational value, and is not overly difficult to implement. Technical capability also demonstrates a strong influence, indicating that firms with mature digital systems are better prepared to integrate AI solutions. In contrast, external environmental pressures did not show a significant role in the adoption process. These findings highlight that internal technological perceptions and readiness are stronger predictors of AI adoption than external forces in operating ICT firms in Pakistan. The study provides insights that can help organizations strengthen their technical readiness and make more confident decisions when transitioning toward AI enabled transformation. This study contributes to AI adoption literature by isolating organizational technical capability and providing national level evidence from an emerging ICT economy.